Situs inversus totalis with esophageal cancer: a case report - Sabireen,; Patel, Gaurav; Patil, Prakash K.; Vala, Azad; Reelkar, Aditya (International Surgery Journal, 2024)
Situs inversus is a rare disorder and its association with esophageal cancer is seldom encountered in clinical practice. Its incidence is 1/8000 to 1/25000 live births. Only 12 cases have been reported in the literature so far. Here, we report a case of esophageal cancer with situs inversus totalis, which was successfully managed by esophago-gastrectomy via a high right thoracoabdominal approach and review the relevant literature. Although the surgery was technically challenging due anatomic reversal of organs, it did not differ from the routine surgery. Moreover, it was observed that with careful recognition of mirror image anatomy preoperatively and during surgery, complications can be avoided.